2004
DOI: 10.1023/b:sers.0000037765.77313.c4
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in Brazilian Children's Friendship Nominations and Peer Sociometric Ratings

Abstract: Empirical studies on children's peer relationships document a number of gender-and age-related patterns in their friendships. One of the most recorded patterns in peer relationships is the tendency to prefer friends of the same sex (e.g., Belle, 1989; Feiring & Lewis, 1987; Pitcher & Schultz, 1983). This phenomenon has been observed in children as young as 33 months (Jacklin & Maccoby, 1978), and appears to increase in intensity with age until middle child

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
(24 reference statements)
0
16
0
3
Order By: Relevance
“…Furthermore, in a meta-analysis of 77 studies examining 18,339 participants aged 3 to 16, Jiang and Cillessen (2005) reported that sociometric status becomes more stable with age. Other researchers have found that children tend to nominate same-sex peers as liked peers and rate opposite-sex peers as disliked peers (Asher & Dodge, 1986;Asher & Hymel, 1981;de Guzman, Carlo, Ontai, Koller, & Knight, 2004;Hayden-Thomson, Rubin, & Hymel, 1987). Thus, an additional goal was to explore grade, sex, and site differences in the impact of using alternate methods to identify socially rejected children.…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%
“…Furthermore, in a meta-analysis of 77 studies examining 18,339 participants aged 3 to 16, Jiang and Cillessen (2005) reported that sociometric status becomes more stable with age. Other researchers have found that children tend to nominate same-sex peers as liked peers and rate opposite-sex peers as disliked peers (Asher & Dodge, 1986;Asher & Hymel, 1981;de Guzman, Carlo, Ontai, Koller, & Knight, 2004;Hayden-Thomson, Rubin, & Hymel, 1987). Thus, an additional goal was to explore grade, sex, and site differences in the impact of using alternate methods to identify socially rejected children.…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%
“…Despite the heterogeneity within this region of the country and reported socioeconomic differences in prosocial moral reasoning that are relatively small in magnitude of effect (Eisenberg et al, 2001), prior researchers have found commonalities, as well as differences, in moral reasoning across socioeconomic strata within Brazil (Haidt et al, 1993;Nucci et al, 1996). Moreover, in general, Brazil ranks higher than the USA on collectivism and, like many other Latino cultures, is oriented towards strong familial and communal ties (Hofstede, 1984;Haidt et al, 1993;Carlo et al, 2001;Eisenberg et al, 2001;de Guzman et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Estudos futuros com amostras transculturais poderiam explorar de forma mais aprofundada semelhanças e diferenças na forma como as crianças são avaliadas por seus pares. Porém, algumas semelhanças entre características da avaliação sociométrica de crianças brasileiras e americanas já foram observadas em outros estudos, como a preferência por colegas de mesmo sexo e nomeação negativa de mais colegas do sexo oposto (Guzman, Carlo, Ontai, Koller, & Knight, 2004).…”
Section: Inteligência Emocional Aceitação Social E Avaliação De Atriunclassified